2009
DOI: 10.1111/j.1749-6632.2009.04454.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Feeding‐delaying Factors from the Silkworm Bombyx mori

Abstract: In several phytophagous insects, feeding behavior occurs regularly. Recently, we demonstrated that feeding behavior in larvae of the silkworm Bombyx mori had a regular frequency. To address the control of the feeding cycle in B. mori, we aimed to characterize factors influencing feeding initiation and termination. Injection of extracts of the midgut, foregut, and fat body into starved Bombyx larvae delayed the initiation of feeding. This result indicates the presence in these tissues of factors capable of decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Bombyx mori larvae harbour various peptides that regulate feeding behaviour. Some of these peptides are synthesized or recognized in the brain (Nagata et al, 2009(Nagata et al, , 2011a(Nagata et al, , 2011b(Nagata et al, , 2012. Previous studies revealed that BmNPV infection in the brain is crucial for the induction of host manipulation (Katsuma et al, 2012;Kokusho et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Bombyx mori larvae harbour various peptides that regulate feeding behaviour. Some of these peptides are synthesized or recognized in the brain (Nagata et al, 2009(Nagata et al, , 2011a(Nagata et al, , 2011b(Nagata et al, , 2012. Previous studies revealed that BmNPV infection in the brain is crucial for the induction of host manipulation (Katsuma et al, 2012;Kokusho et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, significant feeding inhibitory factors that prolong the latency to the initiation of feeding (feeding-delaying activity) were observed in the extracts of the intestine (foregut, midgut) of B . mori larvae [17]. A previous biochemical study showed that B .…”
Section: Introductionmentioning
confidence: 99%
“…These two physiologically defined feeding states, hunger and satiety, support the evaluation of feeding behavior in B. mori larvae by measuring the latency period prior to the initiation of feeding (Nagata et al, 2011b). We were previously able to identify several biologically active peptides as feeding modulators by measuring the length of the latency period prior to the initiation of feeding in B. mori larvae (Nagata et al, 2009, 2011a,b). Among these peptides, two classes of peptides with different biological activities on feeding behavior were characterized: (1) inhibitory peptides, which prolong the latency to the initiation of feeding, and (2) acceleratory peptides, which shorten the latency to feeding initiation.…”
Section: Introductionmentioning
confidence: 99%